ANALYSIS OF FACTORS FOR PRODUCT ATTRIBUTES, SATISFACTION AND LOYALTY OF HYPERMARKET CUSTOMERS IN MALANG CITY (International Conference of Graduate School on Sustainability (ICGSS), 2018)
The purpose of this study is to analyze the confirmatory factors of product attributes, satisfaction and loyalty of hypermarket customers in Malang City. This research was conducted on giant hypermarket customers in Malang City, using a sample size of 120 respondents. Sampling with Convenience sampling technique. The collected data were analyzed using confirmatory factor analysis. Based on the confirmatory factor analysis test proved that the indicator of the completeness of various strongest products as a form of product attribute variables. Indicators of product price suitability with the strongest expectations as forming customer satisfaction variables and indicators of the desire to always shop at the strongest giant hypermarket as a form of customer loyalty variables.